2017
DOI: 10.1055/s-0042-124506
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of the Use of Pedometers in Individuals with Bipolar Disorder

Abstract: Before patients with bipolar disorder (BD) can begin to perform balanced physical activity, they have to overcome many difficulties. The aim of this study was to examine the acceptance of pedometers as a self-assessment tool in people with BD. Patients who participated in an intervention study with body-oriented groups and psychoeducation groups at the Medical University of Graz/ Department of Psychiatry were invited to use pedometers on a daily basis and keep pedometer diaries over a period of 24 weeks. Most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Danner et al determined that patients with bipolar disorder were highly satisfied with the use of a pedometer. 31 Pedometer-based interventions to increase physical activity in people with chronic paralysis were reported to be pleasing (80%). 32 It is stated that pedometers have an activating feature for individuals with their visual feedback feature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Danner et al determined that patients with bipolar disorder were highly satisfied with the use of a pedometer. 31 Pedometer-based interventions to increase physical activity in people with chronic paralysis were reported to be pleasing (80%). 32 It is stated that pedometers have an activating feature for individuals with their visual feedback feature.…”
Section: Discussionmentioning
confidence: 99%
“…33 Additionally, patients think that pedometers increase motivation for exercise and provide benefits to their health. 31 Another study determined that 93.7% of older adults would recommend a gait intervention to a friend, which included a pedometer, educational material, and group discussions. 34 Mendoza et al revealed that the step count in the group followed with a pedometer was higher than the control group followed with a diary at the end of 3 months among patients with COPD.…”
Section: Discussionmentioning
confidence: 99%